Optimization of the Thermal Environment of Large-Scale Open Space with Subzone-Based Temperature Setting Using BEM and CFD Coupling Simulation - Qihang Zhang; Qinli Deng; Xiaofang Shan; Xin Kang; Zhigang Ren (Energies, 2023)
A cruise ship, which has large-scale open spaces, has an uneven cabin thermal environment in the cruise public space, leading to overcooling or poor cooling issues. Therefore, optimizing the thermal environment of public spaces during a cruise should be the priority. According to the space functions of the cruise ship, the large public space is divided into three subzones: the entertainment area (Subzone I), the round-table dining area (Subzone II), and the square-table dining area (Subzone III). To create a uniform, stable, and comfortable thermal environment, this study proposes a subzone-based temperature setting approach to independently adjust the thermal environment of each subzone. Coupling simulation of building energy modeling (BEM) and computational fluid dynamics (CFD) was adopted in this study to determine proper temperature setpoints of the subzones under different occupancy rates. The results indicate that, compared with a single-temperature setpoint for the entire public space, the subzone-based temperature setpoints could achieve a uniform thermal environment. The average temperature difference among the three subzones was 0.68 °C. Moreover, the airflow between two adjacent subzones considerably affected the BEM results of energy consumption of the air-conditioning system.